The Distribution and Accessibility of Geologic Targets near the Lunar South Pole and Candidate Artemis Landing Sites - Kring, David A. (David Allen); Barrett, Natasha; Bickel, Valentin Tertius; Satyakumar, Animireddi V.; Halim, Samuel; Gawronska, Aleksandra; Harish; Shah, Jahnavi; Boazman, Sarah (The Planetary Science Journal, 2022)
Transformative lunar science will be driven by the accessibility, recovery, and return to Earth of geological specimens. Isolated boulders, rock exposures, and rocky craters at the lunar south pole all provide opportunities for geologic characterization and sampling of the lunar crust. Here, we present the results of orbital geological mapping of the region surrounding the south pole using Lunar Reconnaissance Orbiter Narrow Angle Camera images (0.5–2 m pixel−1). We mapped the distribution of isolated boulders (86,896), rocky craters (3556), and rock exposures (7553) around potential Artemis landing sites 001 and 004 (NASA 2020), which are within or near one of the Artemis III candidate landing regions. We found that boulder abundance decreases with increasing distance from the rim of Shackleton crater. From that correlation, we infer that most of the boulders and rock exposures near Shackleton were deposited as ejecta by the Shackleton impact, and by later the reworking of that material during smaller impact events. We additionally assessed the accessibility of the mapped features, and documented geologic targets located on shallow (<15°) slopes, including those on the Shackleton crater rim and on the “Connecting Ridge” between Shackleton and Henson crater. Such targets could be sampled by a future mission to the lunar south pole region. Our catalog of mapped features is made available to the lunar community. Sarah. J. Boazman; Jahnavi Shah; Harish; Aleksandra J. Gawronska; Samuel H. Halim; Animireddi V. Satyakumar; Cosette M. Gilmour; Valentin T. Bickel; Natasha Barrett; David A. Kring